Comparative analysis of complete chloroplast genomes of Cousinia (Asteraceae) species - Karimov, Boburbek; Tojibaev, Sh. Komiljon; Azimova, Dilnoza; Yusupov, Ziyoviddin; Liu, Lufeng (Frontiers in Plant Science, 2025)
The study focused on analyzing the chloroplast genome structure and investigating the phylogenetic relationships among six species of the Cousinia genus. Within the Asteraceae family, the complete chloroplast genome sequences of six Cousinia species, ranging from 152,553 to 152,619 bp. The chloroplast genomes exhibit a characteristic quadripartite structure. The gene order is largely conserved across the genus, with an exception in the small single copy region, where a reverse orientation is observed in comparison to Cousinia thomsonii. A total of 131 genes were annotated, including 87 protein-coding genes, 36 tRNA genes, and 8 rRNA genes, with 18 genes showing duplication. Notably, 16 genes contain introns, with ycf3 and clpP carrying two introns each. Nucleotide diversity analysis revealed 412 polymorphic sites across 152,892 nucleotides in six Cousinia species. Higher nucleotide polymorphism levels were found in trnE-UUC – rpoB, trnL-UAA – trnF-GAA – ndhJ, rbcL, and ycf1 genomic regions, indicating possible genomic loci for species differentiation. Phylogenetic analysis using complete chloroplast genomes, demonstrated the genus Cousinia’s phylogenetic placement within the Cardueae tribe, forming distinct clades that align with its traditional sectional classification. The Arctiinae subtribe, containing Cousinia, forms a monophyletic group with Arctium lappa, while Saussureinae were found to be polyphyletic. The findings suggest that while morphological traits are valuable in taxonomy, they may provide limited resolution compared to the more comprehensive phylogenetic insights obtained from chloroplast genome analysis.